Establishing content-validity of a disease-specific health-related quality of life instrument for patients with chronic hypersensitivity pneumonitis - Kerri I. Aronson; Maha Ali; Evgeniya Reshetynak; Robert J. Kaner; Fernando J. Martinez; Monika M. Safford; Laura C. Pinheiro (SpringerOpen, 2021)
Abstract Background Chronic Hypersensitivity Pneumonitis (CHP) is caused by an immune mediated response in the lung tissue after exposure to an inhaled environmental antigenic stimulant. We previously documented the ways in which CHP impacts patients' lives and have now developed a disease-specific instrument, the CHP-HRQOL instrument, to measure health-related quality of life (HRQOL). The objective of this study was to assess content validity for the CHP-HRQOL. Methods Cognitive interviews were conducted among adults with CHP. The instrument was revised and refined between each round of interviews. Feedback was obtained on the instructions, items, response options, and recall period. Items where participants had difficulty with comprehension, wording, or misinterpretation were marked by the interviewer and participant feedback was reviewed to make revisions, add or delete items when appropriate. Readability statistics were calculated using Flesch-Kincaid grade level and reading ease scores. Results Ten participants were interviewed over three rounds, with revisions made to the questionnaire in an iterative process. In the initial 39 item instrument, we identified 7 items where two or more participants reported difficulty. Participants preferred a four-week recall period (compared to a two-week recall period) and response options with a 5-point response scale. The final version of the CHP-HRQOL includes 40 items with a median reading level between 6th and 7th grade. Conclusion The CHP-HRQOL instrument demonstrated high content validity and is ready for psychometric testing in further validation studies.